Actividad de la glándula prepucial tubular en dos especies de Canthon (Coleoptera: Scarabaeidae, Scarabaeinae) - Martínez M, Imelda; Linares M., Pascual (Instituto de Ecología, A.C., 1994)
The anatomy and structure of preputial gland, as well as the morphofunctional modifications which appear during the life cycle of Canthon indigaceus chevrolati Harold and Canthon cyanellus cyanellus LeConte, are similar in both species in spite of their very unlike reproductiva behavior. This gland is functional oniy in sexually matura males. Its secretions, consisting primarily of polysaccharides, apparently act as lubrication during initial mating.